NEW METHODS OF ASSESSING THE LEVEL OF D-DIMER IN THE DIAGNOSIS OF PULMONARY E - A. G. Pronin; O. A. Valova (Неотложная медицинская помощь)
BACKGROUND. Pulmonary embolism (PE) is a pathological condition complicating the course of many diseases, which often remains unrecognized. An important role for its diagnosis is given to D-dimer concentration in blood. This marker has a low specificity and a high predictive value of a negative result. The normal level of D-dimer with low clinical probability of pulmonary embolism allows to exclude this diagnosis with an accuracy of 97%. According to the European Society of Cardiologists, the specificity of D-dimer may be improved by the correction of the upper reference values in patients of different age groups. The aim of the study was to calculate the correction coefficient of the normal D-dimer upper limit depending on age in order to improve the diagnosis of pulmonary embolism in patients with chronic heart failure (CHF).MATERIAL AND METHOD. We surveyed 160 patients over 50 years with suspected pulmonary embolism on the background of CHF of III-IV functional class according to NYHA classification. All patients underwent clinical and biochemical blood tests, d-dimer, echocardiography, Doppler ultrasound, angiography of pulmonary arteries. Based on the results of examination, the diagnosis of pulmonary embolism was set in 102 patients with heart failure of III-IV functional class according to NYHA classification. The level of the proximal occlusion was distributed as follows: main pulmonary artery — 41%, lobar artery — 31%, segmental artery — 28% of patients. All patients had not a high risk of death from pulmonary embolism. In 58 patients with CHF of III–IV functional class and D-dimer above reference values, PE was excluded.RESULTS AND CONCLUSION. In patients with CHF of III–IV functional class (NYHA) over 50 years, the correction of upper limit of D-dimer reference with a coefficient of 0.012 allows to increase the specificity of this marker in the diagnosis of pulmonary embolism by 40%.